Peran Auditor Internal Dalam Consulting Perusahaan - Subekti Catur Oktarisa; Wiwik Supratiwi (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
This study examines the added value that businesses can derive from internal auditors through their consulting role. This is research that provides an overview of consulting activities in a business context. In today's complexity and constantly changing business issues, leveraging the wealth of collective business information obtained by internal auditors to add value and enhance competitiveness is therefore a good strategy. Under stewardship theory, internal audit will support the board and management team through a consulting role and are expected to provide advice on business improvements or future investment opportunities if the company is aggressive for new ventures, etc. This research is a literature review that discusses the nature and level of consulting activity in a company. The results show that internal auditors provide consultation at the request of management, the board of directors or the audit committee, on an ad-hoc basis to help improve business operations and to achieve organizational goals. This study contributes to the literature by providing deeper insight into the nature and level of consulting activity carried out by internal auditors.